2020
DOI: 10.1002/bin.1708
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of parent reading interventions on improving reading fluency of students with reading difficulties

Abstract: The current study examines the effect of parent reading interventions on the reading fluency of students with reading disabilities. The experimental procedure was carried out in two stages. In the first stage, the Brief Experimental Analysis procedure was followed to determine the most effective reading fluency intervention for all participants, and in the next step, the parental delivery of the selected intervention procedure took place. Brief experimental analysis was used to identify appropriate reading flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…All in all, the strategy, based on Mayer's SOI model [10], is structured into selecting, organizing, and integrating, so that the sequence allows for the identification of keywords and their meanings (lexical processing), for the expression and management of adequate grammar structure (syntactic processing), and for the relation of main ideas in order for the global meaning of a text to be grasped (semantic processing). Since this is a structurebased strategy, students who have been using it have shown improvement in lexical and syntactic processing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All in all, the strategy, based on Mayer's SOI model [10], is structured into selecting, organizing, and integrating, so that the sequence allows for the identification of keywords and their meanings (lexical processing), for the expression and management of adequate grammar structure (syntactic processing), and for the relation of main ideas in order for the global meaning of a text to be grasped (semantic processing). Since this is a structurebased strategy, students who have been using it have shown improvement in lexical and syntactic processing.…”
Section: Discussionmentioning
confidence: 99%
“…As stated by Mayer [10], the process leading to learning depends both on the way students process information and on the materials being presented to them. In this sense, the usage of the computerized strategy is relevant and may be fostering positive achievements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…to deliver a brief, focused intervention that provides additional opportunities for students to receive instruction and practice with key academic skills. Parent tutoring has been effective in (1) improving math skills in students at risk for math problems (Heller & Fantuzzo, 1993); (2) increasing reading skills in students with attention-deficit/hyperactivity disorder (ADHD; Hook & DuPaul, 1999); (3) improving reading and vocabulary skills of students who have limited English proficiency (Cooke et al, 2009;Kupzyk et al, 2011b;); and (4) increasing reading skills in students at-risk for or identified with learning disabilities (Doǧanay Bilgi, 2020;Erion & Hardy, 2019;Gortmaker et al, 2007;Kupzyk & Daly, 2017;Persampieri et al, 2006;Valleley et al, 2005;Zhou et al, 2019). Parent tutoring can promote skill generalization and maintenance as students have more opportunities to respond to multiple exemplars and with diverse instructors.…”
mentioning
confidence: 99%